Uptake and translation of skeletal muscle myosin messenger ribonucleoprotein particles by primary heart muscle cells in culture - Viljoen, Annalize (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical biochemistry)) - University of Stellenbsoch, 1982.